Utilization of light energy in phototrophic Gemmatimonadetes - Koblížek, Michal; Dachev, Marko; Bína, David; Nupur; Piwosz, Kasia; Kaftan, David (Journal of photochemistry and photobiology. B, Biology, 2020)
Gemmatimonas phototrophica is, so far, the only described phototrophic species of the bacterial phylum Gemmatimonadetes. Its cells contain a unique type of photosynthetic complex with the reaction center surrounded by a double ring antenna, however they can also grow in the dark using organic carbon substrates. Its photosynthesis genes were received via horizontal gene transfer from Proteobacteria. This raises two questions; how the horizontally transferred photosynthesis apparatus has integrated into the cellular machinery, and how much light-derived energy actually contributes to the cellular metabolism? To address these points, the photosynthetic reactions were studied on several levels, from photophysics of the reaction center to cellular growth. Flash photolysis measurements and bacteriochlorophyll fluorescence kinetic measurements documented the presence of fully functional type-2 reaction centers with a large light harvesting antenna. When illuminated, the bacterial cells reduced their respiration rate by 58 ± 5%, revealing that oxidative phosphorylation was replaced by photophosphorylation. Moreover, illumination also more than doubled the assimilation rates of glucose, a sugar that is mostly used for respiration. Finally, light increased the growth rates of Gemmatimonas phototrophica colonies on agar plates. All the presented data provide evidence that photosynthetic complexes are fully integrated into cellular metabolism of Gemmatimonas phototrophica, and are able to provide a substantial amount of energy for its metabolism and growth.
Keywords: kinetika; Photoheterotrophy; fluorescenční spektrometrie; Bacteria; Phosphorylation; bakteriochlorofyly; Gemmatimonadota; Photophosphorylation; Photolysis; Oxidation-Reduction; fotosyntéza; Bacterial Proteins; Spectrometry, Fluorescence; Photosynthetic Reaction Center Complex Proteins; fotosyntetická reakční centra (proteinové komplexy); Photosynthesis; fotolýza; Kinetics; oxidace-redukce; fosforylace; Bacteriochlorophylls; Anoxygenic phototrophs; bakteriální proteiny; Gemmatimonadetes